ERNICA Consensus Conference on the Management of Patients with Esophageal Atresia and Tracheoesophageal Fistula: Diagnostics, Preoperative, Operative, and Postoperative Management - Dingemann, Carmen; Eaton, Simon; Aksnes, Gunnar; Bagolan, Pietro; Cross, Kate M.; De Coppi, Paolo; Fruithof, JoAnne; Gamba, Piergiorgio; Husby, Steffen; Koivusalo, Antti; Rasmussen, Lars; Sfeir, Rony; Slater, Graham; Svensson, Jan F.; Van der Zee, David C.; Wessel, Lucas M.; Widenmann-Grolig, Anke; Wijnen, Rene; Ure, Benno M. (European Journal of Pediatric Surgery, 2020)
Introduction Many aspects of the management of esophageal atresia (EA) and tracheoesophageal fistula (TEF) are controversial and the evidence for decision making is limited. Members of the European Reference Network for Rare Inherited Congenital Anomalies (ERNICA) conducted a consensus conference on the surgical management of EA/TEF based on expert opinions referring to the latest literature.Materials and Methods Nineteen ERNICA representatives from nine European countries participated in the conference. The conference was prepared by item generation, item prioritization by online survey, formulation of a final list containing the domains diagnostics, preoperative, operative, and postoperative management, and literature review. The 2-day conference was held in Berlin in October 2018. Anonymous voting was conducted via an internet-based system. Consensus was defined when 75% of the votes scored 6 to 9.Results Fifty-two items were generated with 116 relevant articles of which five studies (4.3%) were assigned as level-1evidence. Complete consensus (100%) was achieved on 20 items (38%), such as TEF closure by transfixing suture, esophageal anastomosis by interrupted sutures, and initiation of feeding 24 hours postoperatively. Consensus ≥75% was achieved on 37 items (71%), such as routine insertion of transanastomotic tube or maximum duration of thoracoscopy of 3 hours. Thirteen items (25%) were controversial (range of scores, 1–9). Eight of these (62%) did not reach consensus.Conclusion Participants of the conference reached significant consensus on the management of patients with EA/TEF. The consensus may facilitate standardization and development of generally accepted guidelines. The conference methodology may serve as a blueprint for further conferences on the management of congenital malformations in pediatric surgery.
Keywords: esophageal atresia; European Reference Network on Rare Inherited and Congenital Anomalies (ERNICA); surgical management; evidence; consensus conference